OPTIMALISASI KETERBATASAN SARANA DAN PRASARANA SEKOLAH DALAM RANGKA MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI 1 KEBON JERUK - Ria Nopitasari; Eliza Charlina; Jemi Adi Sastra; Muhammad Kaulan Karima (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning in schools is inextricably linked to facilities and infrastructure. This article examines strategies for optimizing the limited facilities and infrastructure at SD Negeri 1 Kebon Jeruk to improve the quality of learning processes and outcomes. Facilities and infrastructure are fundamental to the implementation of effective learning in elementary schools. Limited facilities and infrastructure remain a major obstacle to the implementation of learning in many elementary schools. The management of facilities and infrastructure is a crucial aspect of school management to help achieve educational goals. The research method used was descriptive qualitative through literature review, non-participatory observation, and analysis of school documents. Optimizing facilities and infrastructure has been shown to have a positive impact on learning effectiveness and student engagement. Therefore, good management of facilities and infrastructure can help schools achieve educational goals even under limited conditions.